Analisis Selera Konsumen Terhadap Atribut Produk dalam Keputusan Pembelian Minuman Mixue - Salma Aqila Putri; Hamidah Hendrarini; Dona Wahyuning Laily (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Mixue is an ice cream shop with cheap and delicious prices, making Mixue expand massively throughout Indonesia in a fairly short time. This study aims to identify and analyze the characteristics, purchasing decision process and consumer tastes towards the attributes of Mixue beverage products. This research was conducted at the Mixue shop in the Dharmawangsa and Ngagel Surabaya branches. The sampling technique was "accidental sampling" with a total of 84 consumers. The analytical method uses descriptive analysis and Fishbein multi-attribute analysis with the help of a questionnaire and Microsoft Excel 2019. Based on the analysis using Fishbein's multi-attributes, the attribute that has the most interest is price, while the attributes that consumers trust the most are price, brand. Based on the Fishbein score obtained at 101.69, it can be said that consumer tastes for Mixue beverage products are included in the like category.